TREND ARTIKEL PROJECT BASED LEARNING PADA PEMBELAJARAN BAHASA DALAM JURNAL TERINDEKS SCOPUS DAN SINTA: DARI DESAIN PENELITIAN HINGGA ANALISIS DATA - Winda Noprina; Dina Fitria Handayani (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Project based Learning (PjBL) has been successful and effective in improving various skills. Numerous studies have shown the success of PjBL. This research used content analysis on several articles that have been published in indexed scopus journals from 2019 to 2022, with PjBL as the main focus of research. The study reveals that the number of publications focusing on PjBL has increased in the past three years. Among those publications, the most dominant research design is quantitative. In addition, practical language classes are the most targeted subject and material. Serial tests and t-tests are the most common instruments used and data analysis methods. In connection with the findings of this research, some recommendations have been proposed for future research to focus on PjBL. Some of these recommendations include increasing the diversity of research types and choosing more appropriate data analysis.